Protamine is an antagonist of apelin receptor, and its activity is reversed by heparin. Issue 6 (27th February 2017) - Le Gonidec, Sophie; Chaves‐Almagro, Carline; Bai, Yushi; Kang, Hye Jin; Smith, Allyson; Wanecq, Estelle; Huang, Xi‐Ping; Prats, Hervé; Knibiehler, Bernard; Roth, Bryan L.; Barak, Larry S.; Caron, Marc G.; et al.
ABSTRACT: Apelin signaling plays an important role during embryo development and regulates angiogenesis, cardiovascular activity, and energy metabolism in adulthood. Overexpression and hyperactivity of this signaling pathway is observed in various pathologic states, such as cardiovascular diseases and cancer, which highlights the importance of inhibiting apelin receptor (APJ); therefore, we developed a cell‐based screening assay that uses fluorescence microscopy to identify APJ antagonists. This approach led us to identify the U.S. Food and Drug Administration–approved compound protamine—already used clinically after cardiac surgery—as an agent to bind to heparin and thereby reverse its anticlotting activity. Protamine displays a 390‐nM affinity for APJ and behaves as a full antagonist with regard to G protein and β‐arrestin–dependent intracellular signaling. Ex vivo and in vivo, protamine abolishes well‐known apelin effects, such as angiogenesis, glucose tolerance, and vasodilatation. Remarkably, protamine antagonist activity is fully reversed by heparin treatment both in vitro and in vivo . Thus, our results demonstrate a new pharmacologic property of protamine—blockade of APJ—that could explain some adverse effects observed in protamine‐treated patients. Moreover, our data reveal that the established antiangiogenic activity of protamine would rely on APJ antagonism.—Le Gonidec, S., Chaves‐Almagro, C., Bai, Y., Kang, H. J., Smith, A., Wanecq, E., Huang, X.‐P., Prats, H., Knibiehler, B., Roth, B. L., Barak, L. S., Caron, M. G., Valet, P., Audigier, Y., Masri, B. Protamine is an antagonist of apelin receptor, and its activity is reversed by heparin. FASEB J. 31, 2507–2519 (2017). www.fasebj.org